The effects of a combination of ion channel inhibitors in female rats following repeated mild traumatic brain injury - Mao, Yilin; Black, A.; Milbourn, H.; Krakonja, S.; Nesbit, Michael; Bartlett, C.; Fehily, B.; Takechi, Ryu; Yates, N.; Fitzgerald, Melinda (MDPI AG, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Following mild traumatic brain injury (mTBI), the ionic homeostasis of the central nervous system (CNS) becomes imbalanced. Excess Ca2+ influx into cells triggers molecular cascades, which result in detrimental effects. The authors assessed the effects of a combination of ion channel inhibitors (ICI) following repeated mTBI (rmTBI). Adult female rats were subjected to two rmTBI weight-drop injuries 24 h apart, sham procedures (sham), or no procedures (normal). Lomerizine, which inhibits voltage-gated calcium channels, was administered orally twice daily, whereas YM872 and Brilliant Blue G, inhibiting a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and P2X7 receptors, respectively, were delivered intraperitoneally every 48 h post-injury. Vehicle treatment controls were included for rmTBI, sham, and normal groups. At 11 days following rmTBI, there was a significant increase in the time taken to cross the 3 cm beam, as a sub-analysis of neurological severity score (NSS) assessments, compared with the normal control (p < 0.05), and a significant decrease in learning-associated improvement in rmTBI in Morris water maze (MWM) trials relative to the sham (p < 0.05). ICI-treated rmTBI animals were not different to sham, normal controls, or rmTBI treated with vehicle in all neurological severity score and Morris water maze assessments (p > 0.05). rmTBI resulted in increases in microglial cell density, antioxidant responses (manganese-dependent superoxide dismutase (MnSOD) immunoreactivity), and alterations to node of Ranvier structure. ICI treatment decreased microglial density, MnSOD immunoreactivity, and abnormalities of the node of Ranvier compared with vehicle controls (p < 0.01). The authors’ findings demonstrate the beneficial effects of the combinatorial ICI treatment on day 11 post-rmTBI, suggesting an attractive therapeutic strategy against the damage induced by excess Ca2+ following rmTBI.